AI Awareness, Literacy, and Social Influence Predict Ethical Reasoning and Responsible Use in Higher Education - Nurul Febrianti; Aristia Anastasya Diandra; Andi Dio Nurul Awalia; Della Fadhilatunnisa; M. Miftach Fakhri (PT. Academic Bright Collaboration, 2026)
Purpose – This study investigates how AI awareness, AI literacy, and social influence shape students’ AI ethics and, consequently, responsible AI use in higher education.Design/methods/approach – A quantitative cross-sectional survey was conducted with 101 university students in South Sulawesi, Indonesia, who had experience using AI-based learning tools. Data were analyzed using partial least squares structural equation modeling to assess measurement validity and test structural relationships, including the mediating role of AI ethics.Findings – AI awareness and AI literacy have significant positive effects on AI ethics, with AI literacy emerging as the strongest predictor. Social influence shows a significant negative association with AI ethics, indicating that unregulated peer and environmental pressure may encourage AI adoption while weakening ethical sensitivity. AI ethics significantly predicts responsible AI use and mediates the effects of AI awareness, AI literacy, and social influence on responsible use. These results highlight that responsible AI engagement depends not only on cognitive readiness but also on the ethical norms governing how AI is used in academic contexts.Research implications/limitations – The study is limited by its cross-sectional design, self-reported data, and a sample restricted to one region, which may limit causal inference and generalizability.Originality/value – This study provides empirical evidence that AI ethics is a central mechanism linking cognitive and social factors to responsible AI use, informing institutional AI governance, literacy programs, and ethical policy development in higher education.